Neutrophil extracellular traps in acute coronary syndrome - Yawen Wu; Shilin Wei; Xiangyang Wu; Yongnan Li; Xue Han (BMC, 2023)
Abstract Acute coronary syndrome (ACS) is a group of clinical syndromes caused by acute myocardial ischemia, which can cause heart failure, arrhythmia and even sudden death. It is the major cause of disability and death worldwide. Neutrophil extracellular traps (NETs) are reticular structures released by neutrophils activation and have various biological functions. NETs are closely related to the occurrence and development of ACS and also the subsequent damage after myocardial infarction. The mechanisms are complex and interdependent on various pathways, which require further exploration. This article reviewed the role and mechanism of NETs in ACS, thereby providing a valuable reference for the diagnosis and clinical treatment of ACS.